Healthy but mortal : human biology and the first farmers of western Europe - Jackes, Mary
What do we know about the effects of the transition to agriculture on human biology? A literature has grown up that gives us the impression that we know a great deal about what happened to bones and teeth when people became sedentary farmers. A review of the sources of these ideas and the evidence supporting them, especially based on work in Portugal, reveals that a reconsideration of the biological consequences of farming in Europe is overdue.